2009
DOI: 10.1074/jbc.m109.038646
|View full text |Cite
|
Sign up to set email alerts
|

Induced Dimerization of the Amyloid Precursor Protein Leads to Decreased Amyloid-β Protein Production

Abstract: The amyloid precursor protein (APP) plays a central role in Alzheimer disease (AD) pathogenesis because sequential cleavages by ␤-and ␥-secretase lead to the generation of the amyloid-␤ (A␤) peptide, a key constituent in the amyloid plaques present in brains of AD individuals. In several studies APP has recently been shown to form homodimers, and this event appears to influence A␤ generation. However, these studies have relied on APP mutations within the A␤ sequence itself that may affect APP processing by int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
142
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(155 citation statements)
references
References 54 publications
13
142
0
Order By: Relevance
“…APP and its mammalian homologs, the APP-like proteins, can form intracellular homo-and heterodimers; although APP is monomeric in solution in vitro, it dimerizes in the presence of heparin (Gralle et al, 2006), thus possibly reducing Ab generation (Eggert et al, 2009). The E2 domain of APP-like protein 1 crystallizes as a dimer, and a heparin hexasaccharide soaked into the crystal is bound asymmetrically within the dimer, making different contacts with the two protein monomers; one heparin oligosaccharide is bound to each dimer (3QMK) (Xue et al, 2011).…”
Section: F Protein Aggregation In the Nervous Systemmentioning
confidence: 99%
“…APP and its mammalian homologs, the APP-like proteins, can form intracellular homo-and heterodimers; although APP is monomeric in solution in vitro, it dimerizes in the presence of heparin (Gralle et al, 2006), thus possibly reducing Ab generation (Eggert et al, 2009). The E2 domain of APP-like protein 1 crystallizes as a dimer, and a heparin hexasaccharide soaked into the crystal is bound asymmetrically within the dimer, making different contacts with the two protein monomers; one heparin oligosaccharide is bound to each dimer (3QMK) (Xue et al, 2011).…”
Section: F Protein Aggregation In the Nervous Systemmentioning
confidence: 99%
“…Surprisingly, A␤ could not be detected for the K28E mutant in cultured cells and the cell-free assay system by SDS-PAGE (data not shown). This may reflect a potential alteration of the folding of Lys-28 mutant A␤ peptides (45), which could possibly have affected their detectability in some of the previous reports (22,46,47 FIGURE 4. Validation of cell-free assay system concerning the cleavage specificity of purified ␥-secretase on mutant APP C-terminal fragment based C100-His 6 substrates.…”
Section: Fad Mutants In the ␥-Secretase Cleavage Site Regionmentioning
confidence: 99%
“…This region is known to be critical for A␤ aggregation (19 -21), and aggregation inhibitors interacting with this region also act as GSMs (18). However, a recent study demonstrated that dimerization per se might not be a factor that determines ␥-secretase cleavage specificity (22), and whether GXXXG mutants inhibit dimerization is controversial (23). In addition, the lack of a consistent response to GSMs regarding an inversely correlated production of A␤ 42 and A␤ 38 by PS FAD mutants observed earlier argued against a strict precursor-product relationship between A␤ 42 and A␤ 38 (24,25).…”
mentioning
confidence: 99%
“…1) (Spencer et al, 1993;Eggert et al, 2009). In contrast to cross-linking antibodies, AP20187 is permeable and is able to target intracellular Fv-PrP.…”
Section: Enforced Prpmentioning
confidence: 99%